Integrating paraffin phase change material in the storage tank of a solar water heater to maintain a consistent hot water output temperature. (October 2021) - Madadi Avargani, Vahid; Norton, Brian; Rahimi, Amir; Karimi, Hajir
Graphical abstract: Highlights: A novel integrated solar water heater system with a PCM unit is proposed. The system can store solar energy during peak radiation periods to meet demand in falling periods. A comprehensive and coupled model is developed for the integrated system. The system can shift the hot water production time from midday to midnight. The system with a single collector can produce up to 300 L hot water at 60 °C during 7 h of system operating. For two consecutive collectors, up to 1200 L hot water for 8 h can be produced. Abstract: The temperature of the hot water withdrawn for a solar water heater varies throughout a day. However, for process heat applications, constant temperature water can be required from a solar water heater. This is usually achieved by providing additional auxiliary heat input. Disadvantageously, such extra water heating incurs additional cost and, if met from fossil fuels, produces greenhouse gas emissions. An alternative approach of using a phase change material to moderate variations in the outlet temperature of hot water from the store is examined in this paper using an experimentally-validated CFD model of a solar water heater with a phase change material thermal energy storage in the hot water tank. The CFD model was solved by COMSOL Multiphysics. For a particular solar water heating system, incorporating an encapsulated paraffin wax phase change material has been shown to able to deliver up to 1200 L of hot water at a temperature of 60 °C ± 2 °C for more than 8 h.